2013
DOI: 10.1136/annrheumdis-2013-204308
|View full text |Cite
|
Sign up to set email alerts
|

The spatial organisation of joint surface chondrocytes: review of its potential roles in tissue functioning, disease and early, preclinical diagnosis of osteoarthritis

Abstract: Chondrocytes display within the articular cartilage depth-dependent variations of their many properties that are comparable to the depth-dependent changes of the properties of the surrounding extracellular matrix. However, not much is known about the spatial organisation of the chondrocytes throughout the tissue. Recent studies revealed that human chondrocytes display distinct spatial patterns of organisation within the articular surface, and each joint surface is dominated in a typical way by one of four basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 63 publications
0
64
0
1
Order By: Relevance
“…As discussed, proliferation-induced changes in the SCSO of human AC and formation of cell clusters are early OA marker [10,14]. Increased expression of the proliferation markers cyclin D1 ( CCDN1 ) and cyclin dependent kinase 6 (CDK6) has been observed in human OA AC compared to healthy control AC [142].…”
Section: Inflammatory Cytokine Signalingmentioning
confidence: 99%
See 3 more Smart Citations
“…As discussed, proliferation-induced changes in the SCSO of human AC and formation of cell clusters are early OA marker [10,14]. Increased expression of the proliferation markers cyclin D1 ( CCDN1 ) and cyclin dependent kinase 6 (CDK6) has been observed in human OA AC compared to healthy control AC [142].…”
Section: Inflammatory Cytokine Signalingmentioning
confidence: 99%
“…Of particular interest, it has been shown that, when human AC samples are fluorescence-tagged and viewed from above, the cells exhibit complex patterns of arrangement in the surface layer of the superficial zone and with an orientation parallel to the joint surface, a feature that has been called superficial cell spatial organization (SCSO) [10,11]. The human SCSO can be highly dynamic, as horizontally orientated cell strings, for example in intact knee AC progress in early OA into double strings, together with an increased SZ cell density suggesting AC cell proliferation, are typical [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Osteoarthritis (OA) is characterized by the degeneration of articular cartilage and subchondral bone and accompanied by joint pain, swelling and stiffness, leading to joint dysfunction [1,2]. Many different factors, including genetics, lifestyle and joint instability contribute to the onset and progression of OA, which greatly affects quality of life in elder population [3].…”
Section: Introductionmentioning
confidence: 99%